Pengaruh Online Customer Review, Shipping Cost dan Payment Method Terhadap Keputusan Pembelian Pada Generasi Z Di Kecamatan Pancur Batu - Ramadani, Ika Ramadani (JEBIM Prima, 2023)
This study aims to determine the effect of online customer reviews, shipping costs and payment methods on purchasing decisions for Generation Z Lazada application users in Pancur Batu District. This type of research is associative which is research with the aim of knowing the effect of two or more variables. The population in this study were all people in Pancur Batu District who had made purchases at Lazada at least twice. The sampling method used purposive sampling. The number of samples used in this study were 100 respondents. The data analysis method in this study linear regression analysis test using Statistical Package For the Social Science For Windows (SPSS). The results of this study indicate that online customer reviews, shipping cost and payment method partially and simultaneously have a positive and significant effect on purchasing decisions decisions for Generation Z Lazada application users in Pancur Batu District. The coefficient of determination is obtained 0.847. This states that the variables of online customer review, shipping cost and payment method influence purchasing decisions by 84.7%, and the remaining 15.3% is influenced by other variables not discussed in this study.